1997
DOI: 10.1007/s002619900188
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance of liver cell adenoma: CT and MR imaging

Abstract: We report the disappearance of liver cell adenoma, documented by computed tomography (CT) and magnetic resonance (MR) imaging. A 42-year-old woman with a diagnosis of hepatic adenoma was followed up by CT and MR imaging after cessation of oral contraceptive use. At the time of diagnosis, the adenoma was 4 cm in diameter and appeared hypervascular on CT. At MR imaging, the lesion was hypointense on T1-weighted sequences, and hyperintense on T2-weighted sequences. The lesion disappeared 4 years after cessation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Furthermore, as has been reported since the late 1970s, intake of OCs could potentially play a role in the enlargement of existing HCAs. To date, discontinuation of OC usage is still the advice given to patients that are diagnosed with an HCA, 13 as several reports showed regression in size of the HCAs after cessation of OC intake 9,39,40 . However, some case reports suggested that discontinuation of OCs will not abort the risk of malignant transformation 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as has been reported since the late 1970s, intake of OCs could potentially play a role in the enlargement of existing HCAs. To date, discontinuation of OC usage is still the advice given to patients that are diagnosed with an HCA, 13 as several reports showed regression in size of the HCAs after cessation of OC intake 9,39,40 . However, some case reports suggested that discontinuation of OCs will not abort the risk of malignant transformation 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…6. Little is known concerning the growth and involution of liver nodules (either HCA or FNH), and this aspect deserves further study [32][33][34][35]. A small isolated nodule (measuring a few millimeters) without the characteristic features of classical FNH could be a FNH precursor [15] or a microadenoma [36].…”
Section: Problem Areas Requiring Further Clarificationmentioning
confidence: 99%
“…In our institution, all patients suspected of having HA were operated and the outcome of conservative management could not be assessed. This is an important issue, as some studies advise resection of HA only, when they are larger than 5 cm, because of the tendency of regression of smaller HA [4,10,16,17] . However, only half of these tumors were found to regress on long-term follow-up [4] , and we believe, together with others, that adenomas should be removed with an open [2,7,18,19] or laparoscopic approach [20,21] , regardless of size.…”
Section: Management Of Solitary-uncomplicated Hamentioning
confidence: 99%